Lead Acid Battery Recycling in the Current Tanzania Industrialization Drive: Challenges and Opportunities - Kaombe, Divina D.; Katemi, Richard J. (Tanzania Journal of Engineering and Technology, 2023)
Advancements in automotive technologies, Information and Communications Technology and renewable energy technologies have increased the use of lead acid batteries as a source of portable and rechargeable energy. This has considerably increased the number of spent batteries with adverse effects on the environment and human health; which calls for recycling of spent batteries. This work was conducted to investigate challenges facing the formal business of recycling spent batteries and potential manufacturers of new lead-acid batteries in Tanzania. The work involved collection of information from key stakeholders such as collectors, dealers, Tanzania Revenue Authority and recyclers. It was found out that about 2 million units of used batteries are available in Tanzania annually; weighing a total of about 8,440 tonnes. At the moment of conducting this work, only two recycling plants were in operation: Ok Plast ltd and Gaia Eco-Solutions (T) Ltd. The two operational ULAB recycling plants process about 6,000 tonnes per year. Despite the large number of spent batteries available annually, the amount received by the two recycling plants is far less than the number of spent batteries available in country. Gaia plant processes about 3,600 tonnes of spent lead batteries per year while OK-Plast is only about 1,500 tons/year. The study revealed existence of illegal exportation of ULAB which is against national Regulations and the Basel International Convention. A number of challenges and opportunities have been discussed. Despite of the challenges, the local ULAB recycling industry in Tanzania is encouraged to explore opportunities of manufacturing new batteries. A number of recommendations have been provided; however, enforcement of the export ban of used Lead Acid Batteries has been stressed. Keywords: Lead acid battery (LAB), Recycling, Spent/used lead acid batteries (ULAB)